PENERAPAN METODE PROBLEM SOLVING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Baiq Fatmawati (UNIVERSITAS HAMZANWADI, 2016)
Student activities in biology learning are still less active. This can be seen from the rarity of students issuing ideas / ideas because the teaching methods carried out still apply conventional methods. Conventional methods rarely provide high-level thinking questions or tasks such as solving problems, especially in critical and creative thinking. Generally, given an activity worksheet that is cognitive (memorization / memory). Such learning methods that lead to lack of attention, interest, and motivation of students in following lessons. Based on this, a learning method is needed that can stimulate students to ask, express their opinions, solve problems and practice students 'creative thinking skills, through the application of problem solving methods, potentially improving students' creative thinking skills in learning. This study aims to determine the effect of problem solving methods on the creative thinking ability of students in class X biology. The research is true experimental design. The populations of this study were the second semester students of class X SMA Negeri 1 Sikur in 2012/2013 academic year, totaling seven classes. A sample of research are class X2 as the experimental class and class X6 as the control class. The research instrument used in the study was a creative thinking test in essay form and consisted of six questions. Data analysis techniques by calculating the acquisition of the average value of students' creative thinking group and calculating the value of indicators of creative thinking students using the formula N Gain. The results of data analysis were obtained, namely (1) for the average value of groups in the experimental class 12.45 and for the control class 10.15., (2) N gain creative thinking for the experimental class was (1). Fluency (58.63); (2). Flexibility (53.31); (3). Originality (20.74), while in the control class is (1). Fluency (36.57); (2). Flexibility (34,72); (3). Originality (19,34). This shows that students' creative thinking ability after applied problem solving methods is more improved than learning with conventional methods.